Comparative Analysis of Budget Performance in Nigeria: Pre and Post-Covid-19 Impact - Abdullahi Sule, Sani; Mulyanto, Mulyanto (The Es Accounting And Finance, 2024)
This research investigates the pronounced impact of the Covid-19 epidemic on Nigeria's fiscal performance, evaluating the budget dynamics both before and after the pandemic. The findings reveal a persistent pattern of budget underperformance characterized by revenue shortfalls and a reliance on international loans for budget implementation. This is a notable trend, considering Nigeria's status as an oil-producing nation. The study underscores a concerning aspect wherein the country, traditionally recognized for its oil wealth, finds itself in the paradoxical position of servicing significant debt. The fiscal challenges, exacerbated by the pandemic, have necessitated a closer examination of economic policies and their implications. In response to the economic fallout, the Nigerian government enacted the Economic Sustainability Plan (ESP, 2020) as a comprehensive post-Covid-19 recovery strategy. While this plan holds promise for economic revitalization, the effectiveness of its accompanying policies in addressing the root causes of fiscal challenges remains a crucial aspect to monitor. As the nation grapples with the aftermath of the pandemic, there is a pressing need for meticulous policy implementation to ensure that the Economic Sustainability Plan not only alleviates immediate economic concerns but also serves as a catalyst for long-term, inclusive, and sustainable economic development. This study contributes to the ongoing discourse on Nigeria's economic resilience in the face of external shocks, emphasizing the imperative of sound fiscal management and policy efficacy for a robust recovery.